Improved safety surface access at low cost airports: Kuala Lumpur International Airport, Malaysia case study - Sabar, Rohafiz; Melan, Mustakim; Anuar, Nur Khairiel (2014)
The purpose of this Paper is to evaluate the importance of airport access pedestrian safety based on the specific experiences, supported by an extensive survey, of passengers at Kuala Lumpur International Airport (Malaysia) Low Cost Airport Terminal (KLIA LCT). The survey will allow a ranking and prioritisation to be made, supported by the selected safety preferences of business and leisure passengers, of the most important pedestrian facilities that should be provided for future airport surface access development. To allow a meaningful interpretation of the survey results, the ANOVA (Analyses of Variance) Test to compare the mean of variances or differences between the factors was used to evaluate the relative safety importance of different pedestrian access facilities according to the varying viewpoints of low cost passengers. It is hoped that the results of this Paper will useful both as theoretical guidelines and also as an example of best practise for airport planners who are engaged in the design of safety airport access pedestrian facilities.